STRATEGI MENINGKATKAN KEUNGGULAN BERSAING MELALUI KUALITAS PELAYANAN PADA PT PUTRA USAHA MANDIRI KOTA BATAM - Hendri Herman (JURNAL AKUNTANSI BARELANG, 2018)
This study aims to determine the effect of service quality on competitive advantage at PT Putra Usaha Mandiri Batam City. The population in this study were 120 customers of PT Putra Usaha Mandiri Kota Batam. Determination of the number of samples using Slovin formula, so that the number of samples is 92. The results of the study show that service quality has a significant effect on competitive advantage. R value of 36.1%, which means that competitive advantage can be explained by service quality of 36.1%.